TEKNOLOGI PRODUKSI PUPUK ORGANIK CAIR DARI LIMBAH SAMPAH RUMAH TANGGA DI KELURAHAN LEMPONGSARI, KODYA SEMARANG DENGAN KOMPOSER EM-4 - Wahyuningsih Wahyuningsih; Edy Supriyo (METANA, 2014)
Abstract In Semarang limited landfill waste,new problems.If problems not handled and managed properly,an increase of waste that occur each year could shorten justify the air.In addition,the waste can the quality of natural resources,causing floods,and cause some diseased. Research to be conducted has several specific objectives,as follomposer EM-4.Minimizing the volume of waste in Semarang environment develop a network tool composter for organic fertilizer production of large-scale environmental and examine the addition of decomposers EM-4 the formation of humus to improve the productivity of organic fertilizer in environmentally friendly, operating condition optimization weathering process household waste using waste decomposer EM-4. Composter network of productivity environmentally friendly is expected to replace the function of inorganic fertilizers Research results:the best is on addition EM-4 8 ppm,with the following results:value ratio C/N 14,77;P2O5 1,24%;K2O 0,42%  SNI: ratio C/N 10-20 ;0,1% min P2O5 ;0,2%min K2O Keyword: EM-4 composer,liquid compost organic,organic waste